Fortifying Data Security: Node.js Authentication, Authorization, and the Dark Web Influence in Modern Web Apps - Shah, Sarthak; Anuja Phapale (International Journal of Applied and Advanced Multidisciplinary Research, 2023)
This paper delves into the crucial aspects of authentication and authorization in modern web applications with a focus on enhancing data security. It explores the use of Node.js, a versatile server-side language, for building web applications and discusses the significance of a secure website for establishing trust between clients and servers. The research covers the implementation of authentication using packages and hashing algorithms, emphasizing the importance of "salt" and "pepper" for password security. Authorization methods, including cookies, sessions, and middleware, are also explored. The paper highlights the necessity of robust security measures to safeguard user data from the dark web and points to future directions in web security, including the role of blockchain and artificial intelligence in the WEB3 landscape.